Perfil da produção apícola em unidades familiares no agreste paraibano - Santos , Sebastião Pereira (2017)
Brazilian beekeeping is one of the activities that favors the development of family agriculture. In the northeast region of Brazil, this activity is developed as a family activity, and can generate extra income for the producers. In this way, this work was carried out with the objective of evaluating the profile of the apicultural production in family based productive units in Agreste Paraibano and evaluating the quality of honey produced and marketed according to the type of packaging used in storage. The data collection was carried out continuously from March to May 2017. 30 beekeepers were interviewed in the municipalities of Bananeiras, Dona Inês and Solânea. The choice of properties was made at random. For the analysis of the data, a file containing all the information present in the questionnaire was edited. For the quantitative variables the means were compared by the "t" test. The physical-chemical analyzes were: pH, acidity, water activity (Aw), humidity, ashes, total glycogen, reducing and non-reducing sugars. For the physical-chemical parameters, the "t" test was applied. The results obtained in the physicochemical analyzes show a variation (P <0.05), whose values varied from 21.99 to 19.85%; pH of 3.68 to 3.22, water activity (Aw) of 0.65 to 0,63 and non-reducing sugars of 18.28% to 5.65%. On the other hand, the municipalities did not influence (P> 0.05) the contents of ashes, acidity, total glycogen and reducing sugars. It can be concluded that in relation to the productive aspects the main product exploited is honey, and the municipalities studied present great potential for the growth of beekeeping, mainly because of the potential of the exploitation of the various bee products. Regarding the physical-chemical analyzes, it is concluded that the samples of honeys analyzed are in conformity with the Normative No. 011 of 2000 of the Ministry of Agriculture. It is concluded that the storage form did not interfere in the quality of the analyzed honey.